Dietary composition and overlap among small‐ and medium‐sized carnivores in Flanders, Belgium. Issue 1 (21st November 2021) - Van Den Berge, Koen; van der Veken, Timo; Gouwy, Jan; Verschelde, Pieter; Eeraerts, Maxime
Abstract: There are increasing concerns about the status and population trends of carnivores around the world. Carnivores play an important role in terrestrial ecosystems, as their interactions influence the composition and function of ecological communities. In the context of global change, it is essential to understand the interactions and resource use of carnivores. In this study, we explore the dietary ecology of six small‐ and medium‐sized carnivores (red fox, European badger, European polecat, stoat, stone marten and least weasel) to determine their main food resources and the degree of food overlap in Flanders, Belgium. The studied species differed in their food consumption pattern with some being generalist and some more specialist. The dietary composition among the species was clearly different, although certain species showed considerable overlap for different food types. We also conclude that the differences and overlap in the dietary habits among the species were consistent across seasons. Understanding these relationships among species' populations and their dietary ecology is essential for biodiversity conservation and nature management.